MO‐G‐BRE‐03: Automated Continuous Monitoring of Patient Setup with Second‐Check Independent Image Registration - Jiang, X; Fox, T; Schreibmann, E (Medical physics (Lancaster), 2014)
Purpose: To create a non‐supervised quality assurance program to monitor image‐based patient setup. The system acts a secondary check by independently computing shifts and rotations and interfaces with Varian's database to verify therapist's work and warn against sub‐optimal setups. Methods: Temporary digitally‐reconstructed radiographs (DRRs) and OBI radiographic image files created by Varian's treatment console during patient setup are intercepted and used as input in an independent registration module customized for accuracy that determines the optimal rotations and shifts. To deal with the poor quality of OBI images, a histogram equalization of the live images to the DDR counterparts is performed as a pre‐processing step. A search for the most sensitive metric was performed by plotting search spaces subject to various translations and convergence analysis was applied to ensure the optimizer finds the global minima. Final system configuration uses the NCC metric with 150 histogram bins and a one plus one optimizer running for 2000 iterations with customized scales for translations and rotations in a multi‐stage optimization setup that first corrects and translations and subsequently rotations. Results: The system was installed clinically to monitor and provide almost real‐time feedback on patient positioning. On a 2 month‐basis uncorrected pitch values were of a mean 0.016° with standard deviation of 1.692°, and couch rotations of − 0.090°± 1.547°. The couch shifts were −0.157°±0.466° cm for the vertical, 0.045°±0.286 laterally and 0.084°± 0.501° longitudinally. Uncorrected pitch angles were the most common source of discrepancies. Large variations in the pitch angles were correlated with patient motion inside the mask. Conclusion: A system for automated quality assurance of therapist's registration was designed and tested in clinical practice. The approach complements the clinical software's automated registration in terms of algorithm configuration and performance and constitutes a practical approach to implement safe and cost‐effective radiotherapy.